(untitled) (Global Journal of Management and Business Research, 2017)
The aims of this study is to investigate the dimensions of human resources strategies (selection and appointment, training, incentives and performance evaluation) and its impact on the total quality management (customer focus, continuous improvement, commitment of senior management and decision making based on facts and employee participation) in the Jordanian private hospitals. The study samples was (10) hospitals out of (59) hospital, so questionnaire was designed to investigate the theoretical framework of the independent variable which is (human resources) and its relation with the dependant variable which is (the management of total quality). It has been distributed (15) questionnaires to each hospital of the study samples, were (130) recovered, while (10) were excluded because they were not valid. Where the number of study samples became (120). The hypotheses were tested based on the statistical analysis program. The study shows that there is a statistical significant relation between the human resources strategies and the implementation of the total quality in the Jordanian private hospital.